Proposed strategy for a regional exchange rate arrangement in post-crisis East Asia - Kawai, Masahiro, 1947- 1947- (Policy research working paper, 2000)
A coordinated action by East Asian countries to stabilize their currencies against a common basket of major currencies (broadly representative of their average structure of trade and foreign direct investment) would help stabilize both intraregional exchange rates and effective exchange rates, in a way consistent with the medium-term objective of promoting trade investment and growth in the region